أخلاقية الأدب وأهميتها: القصص القرآني العربي نموذجا - Jamiu Saadullah Abdulkareem; Yaqub Alhaji Abdullahi (Hasanuddin University, 2021)
الملخص يعتبر الأدب مجموع الشعر والنثر الذي يعكس عادات قوم وتقاليدهم في نواحي حياتهم الدينية والثقافية والاقتصادية والاجتماعية والسياسية والإدارية. ولا شك أن الأدب الإسلامي يؤثر اتباع مذهب الفن للحياة والأدب للمجتمع لينتفع دارسو الأدب المتتج وينفعوا غيرهم بفضائل الفن الجميل وأخلاقية مضامين أجناسه. ومن تلك الأجناس الأدبية فن القصة العربية الذي استخدمه الإسلام في ضبط أحوال السابقين، وذلك لدوره الفعَّال في تعليم الأخلاقية وتصقيل عقول دارسيها وتحسين طرق معيشتهم بها. ولتوضيح تلك الحقائق، عرض البحث نماذج من قِصص القرآن لدعم أهمية الأخلاقية واهتمام الإسلام بها. وانتهجت المقالة منهجين هما التاريخي والوصفي. وكان استخدام المنهج التاريخي عند بيان نشأة وتطور الأدب الإسلامي عبر العصور الأدبية العربية، كما تمَّ توظيف المنهج الوصفي لتحليل أخلاقية النماذج القصصية القرآنية المختارة. ومن نتائج الدراسة الإقرار بأن القرآن هو المثل الأعلى في سرد القِصص وتحليلها وتعليلها، بميزته أنه يهدي للسبيل التي هي أقوم في مجالات الحياة. وتوصي المقالة بالتمسك بالآداب الإسلامية لمنافعها المسعِدة. الكلمات المفتاحية: الأخلاقية؛ الأدب؛ القصة؛ الإسلام؛ القرآن؛ العربية. Abstract: Literature refers to the poetry, prose and drama works which present people’s cultural heritage by studying their religious, cultural, economic and socio-political life. It is clear that Islamic literature is a literary school of thought whose motto is “Art for Life Guide, Literature for Social Development” and its artistic means of communication is aimed at guiding people on humanism and materialism for their own benefits and societal development. In another vein, Qur’anic story-telling in Arabic has a significant role in counseling people for ethics and leading them to a bountiful living, therefore this phenomenon led the authors to research into literature morality and its Islamic importance with case study of stories from Qur’anic verses. The methodology employed was both historical and descriptive. The historical method was used in discussing the history of Islamic literature throughout the Arabic literary periods, while descriptive method was adopted in analyzing the Qur’anic stories sampled on morality. It was affirmed that the Qur’an, as a divine revelation, is considered as the best exemplary in story-telling, analysis and guidance for better living. It is therefore recommended that Islamic ethics should be upheld for humanity development. Keywords: Morality; Literature; Islam; Story; Qur’an; Arabic.